Allometric equation of Paraserianthes falcataria (L.) and Anthocephalus cadamba Miq. for estimating carbon stocks - Kinanto Prabu Werdana; Erri Noviar Megantara; Susanti Withaningsih; Yudha Hadiyanto Eka Saputra (Universitas Diponegoro, 2024)
Coal mining can increase land degradation and deforestation, so efforts are needed to ensure land use in post-mining areas. Therefore, mining companies must carry out land reclamation to restore the important function of forests by planting sengon laut (Paraserianthes falcataria (L.)) and burflower tree (Anthocephalus cadamba Miq.). In contrast to mining, which produces emissions and carbon that contribute to global warming, land reclamation helps absorb carbon and produce oxygen for living things. Therefore, a study was carried out to estimate the carbon stocks from reclamation activities at PT. Indobara Borneo. A quantitative approach through Stratified Random Sampling was applied in this study. Carbon estimation is carried out using allometric equations. The allometric equation of Paraserianthes falcataria (L.) is Y = 0.028D2,695, while the allometric equation of Anthocephalus cadamba Miq. is Y = 0.035D2,600. The total carbon stocks for burflower tree plants are 84.51 tons/ha with a CO2 sink potential of 974.73 tons/Ha, while the total carbon stocks for sengon laut plants are 86.18 tons/ha with a CO2 sink potential of 1355.49 tons/ha. The value of CO₂ sink and carbon stock indicates that there are environmental services to restore and improve vegetation.